PENGARUH PENERAPAN MODEL PEMBELAJARAN SYNECTICS TERHADAP KEMAMPUAN MENULIS PUISI BAHASA INDONESIA PADA SISWA KELAS IV UPTD SD NEGERI 285 SOMPE KECAMATAN SABBANGPARU KABUPATEN WAJO - Rosdiah Salam; Hamzah Pagarra; Radia Magfirah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of the lack of poetry writing skills in students. The objectives of this study are: (1) To determine the description of the application of the synectics learning model to poetry writing learning for fourth grade students of UPTD SD Negeri 285 Sompe, Sabbangparu District, Wajo Regency. (2) To determine the poetry writing skills of fourth grade students of UPTD SD Negeri 285 Sompe, Sabbangparu District, Wajo Regency before and after the application of the synectics learning model. (3) To determine the effect of the application of the synectics learning model on the ability to write Indonesian poetry in fourth grade students of UPTD SD Negeri 285 Sompe, Sabbangparu District, Wajo Regency. This study uses a quantitative approach with a quasi- experimental design research design of the nonequivalent control group design type. The population of this study were all students of UPTD SD Negeri 285 Sompe and the sample in this study were fourth grade students of UPTD SD Negeri 285 Sompe consisting of 40 students. Determination using purposive sampling technique with class IV A as the experimental class and class IV B as the control class. Data collection techniques in this study were tests, observations, and documentation. Data analysis techniques used were descriptive statistical analysis and inferential statistics using the Independent sample t-test. The results of the experimental class study 1) the implementation of the learning process by applying the synectics learning model was carried out at meeting I quite well, meeting II was in the good category, and meeting III was in the very good category, 2) The ability to write poetry after applying the synectics learning model showed an increase, this was evidenced by the posttest score which was higher than the pretest score, 3) The synectics learning model had an effect on the poetry writing ability of class IV students of UPTD SD Negeri 285 Sompe, Sabbangparu District, Wajo Regency. So it can be concluded that the application of the synectics learning model is effective in the results of the poetry writing ability test showing an increase.